Latitude 53 : A Decade. (Edmonton : Latitude 53 Society of Artists, 1983)
Achtem, Linda ; Addy, Diane ; Baroque, Alberta ; Albi, Giuseppe ; Alcock, Clive ; Almon, Bert ; Alexander, Sheilagh ; Alston, Denise ; Amerida, L.X. ; Anderson, Fred ; Archer, Violet ; Astor, David ; Aubin, Maurice ; Charlie Austin Trio ; Auto Output ; Bacon, Andrew ; Bagan, Dan ; Bako, Gerda ; Balan, Jars ; Bale, Lee ; Banana, Anna ; Banger, Michael ; Banks, Toby ; Barbier, Sally ; Barbour, Douglar ; Barry, Doug ; Barton, Bob ; Baumann-Rondez, Alice ; Baychuk, Isabel ; Bayley, Gardner ; Bayley, Jonathan ; Beath, Janice ; Beauparlant, Luc ; Belcher, David ; Beliveau, Paul ; Bell, Wade ; Bennett, Richard ; Bentz, Bruce ; Berg, Rick ; Berg, Reinhard ; Bergson, Don ; Berkowitz, B. ; Besant, Derek ; Beug, Lorne ; Beuhler, Launa ; Bienvenue, Marcella ; Bingham, Russell ; Bird, Mark ; Birk, Becky ; Bishop, Bonnie ; Bishop, Heather ; Bjarnson, Dave ; Blais, Denise ; Blashko, Sylvia ; Blitz, Ava ; Bleuthner, John ; Blum, Irene ; Bonneau, Michel ; Bonner, Barbara ; Claude Bolling Ensemble ; Booth, Don ; Borutski, Marie ; Botar, Oliver ; Bradley, Ross ; Braid, Paul ; Brennan, Blair ; Bres, Hendrik ; Bricker, Scott ; Britton, Kelvin ; Brock, Gordon ; Broderick, Diane ; Brodie, Charles ; Brooks, Derek ; Brooks, Jene ; Brownoff, Alan ; Brownoff, Helen ; Burke, Rebecca ; Bull, Art ; Bruun, Chris ; Burcher, Robert ; Burgess, Cathy ; Burke, Mary Louise ; Burton, Velma ; Bushell, Bill ; Cairns, Calvin ; Campbell, Bob ; Camperol, Lucien ; Cantine, Dave ; Cardiff, Janet ; Carleton, Greg ; Carmichael, Robert Ralph ; Cassady, John C.A. ; Castelli, Marianne ; Cave, Jim ; Chalke, John ; Cheop, Frank ; Chenier, Richard ; Chibuk, Noreen ; Chitty, Elizabeth ; Chubb, Briyan ; Church, Dennis ; Cicansky, Vic ; Clancy, John ; Clare, Jim ; Clark, Doug ; Clark, Cathy ; Clarke-Darrah, Ann ; etc.
Touring exhibition
kunstcatalogus